2007
DOI: 10.4049/jimmunol.178.3.1450
|View full text |Cite
|
Sign up to set email alerts
|

F2L, a Peptide Derived from Heme-Binding Protein, Chemoattracts Mouse Neutrophils by Specifically Activating Fpr2, the Low-Affinity N-Formylpeptide Receptor

Abstract: F2L (formylpeptide receptor (FPR)-like (FPRL)-2 ligand), a highly conserved acetylated peptide derived from the amino-terminal cleavage of heme-binding protein, is a potent chemoattractant for human monocytes and dendritic cells, and inhibits LPS-induced human dendritic cell maturation. We recently reported that F2L is able to activate the human receptors FPRL-1 and FPRL2, two members of the FPR family, with highest selectivity and affinity for FPRL2. To facilitate delineation of mechanisms of F2L action in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 38 publications
5
54
0
Order By: Relevance
“…Mouse Fpr2 is expressed by neutrophils, DCs, and microglial cells, and its transcripts are detected at high levels in spleen and lung (23,24). After the testing of the whole set of mouse FPR-related receptors, Gao et al (25) identified Fpr2 as the only mouse receptor responding to F2L. Indeed, mouse neutrophils, which express Fpr2, respond to human F2L (hF2L) and mouse F2L (mF2L) in both calcium flux and chemotaxis assays.…”
Section: Formyl Peptide Receptor-like 2 Is Expressed and Functional Imentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse Fpr2 is expressed by neutrophils, DCs, and microglial cells, and its transcripts are detected at high levels in spleen and lung (23,24). After the testing of the whole set of mouse FPR-related receptors, Gao et al (25) identified Fpr2 as the only mouse receptor responding to F2L. Indeed, mouse neutrophils, which express Fpr2, respond to human F2L (hF2L) and mouse F2L (mF2L) in both calcium flux and chemotaxis assays.…”
Section: Formyl Peptide Receptor-like 2 Is Expressed and Functional Imentioning
confidence: 99%
“…The ability of mF2L to promote chemotaxis of neutrophils through Fpr2 was demonstrated previously (25). We tested further the capacity of mF2L to induce recruitment of DCs and macrophages, which also express the receptor.…”
Section: Biological Activity Of Mf2l On Murine Dcs and Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Boc2 inhibition was relieved by the addition of either the Fpr1 agonist N-formylmethionyl-leucyl-phenylalanine (fMLF) (19) or the Fpr2 agonist F2L (Fig. 5C) (22). Furthermore, low micromolar concentrations of fMLF and F2L are able to induce CXCL2 release by IC-stimulated CG-deficient neutrophils (Fig.…”
Section: Ac2-26 and Mature Cramp Peptides Modulate Neutrophil Effectormentioning
confidence: 94%
“…FPRL1 Since F2L has been reported to induce the chemotactic migration of mouse neutrophils via FPR2 (mouse counterpart of human FPRL1) [15], we tested whether F2L stimulates the chemotactic migration of HUVECs via FPRL1, with the aid of an FPRL1-selective antagonist (WRW 4 ) [18]. The F2L-induced HUVEC chemotaxis was completely inhibited by WRW 4 (Fig.…”
Section: F2l-induced Huvec Chemotactic Migration Is Mediated Bymentioning
confidence: 98%